2014
DOI: 10.1093/ndt/gfu258
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab-associated agranulocytosis in children with refractory idiopathic nephrotic syndrome: case series and review of literature

Abstract: It is important to pay extra attention to this clinically serious delayed-onset complication as it may be accompanied by life-threatening infections such as sepsis. Further clinical studies are needed to clarify its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…15 While more doses may prolong drug-free remission, this may increase the risk of adverse events, such as neutropenia. 18 In the Japanese trial, for example, lymphocytopenia and neutropenia occurred in 17% and 8% of the children, respectively. 14 Results from our study suggest that oral drug-free remission may be up to three times as long in children with a relatively recent diagnosis of SDNS who are maintained in complete remission with steroids alone.…”
Section: Discussionmentioning
confidence: 99%
“…15 While more doses may prolong drug-free remission, this may increase the risk of adverse events, such as neutropenia. 18 In the Japanese trial, for example, lymphocytopenia and neutropenia occurred in 17% and 8% of the children, respectively. 14 Results from our study suggest that oral drug-free remission may be up to three times as long in children with a relatively recent diagnosis of SDNS who are maintained in complete remission with steroids alone.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab is also associated with serious adverse events in children with complicated FRNS/SDNS, including pulmonary fibrosis [28], fulminant myocarditis [29], pneumocystis pneumonia [16], immune-mediated ulcerative colitis [30] and agranulocytosis [31]. After rituximab treatment, hypogammaglobulinemia persists in most patients with decreased immunoglobulin G (IgG) levels before treatment [32].…”
Section: Adverse Events Of Rituximab In Ssns In Childrenmentioning
confidence: 99%
“…In addition, agranulocytosis has been reported as a delayed onset complication of rituximab, a treatment strategy for patients with complicated steroid‐dependent NS. Kamei et al studied 114 refractory NS cases treated with rituximab and reported that 11 patients (9.6%) had episodes of agranulocytosis at a median age of 6.4 years. The exact reason why agranulocytosis develops in this context still needs to be explained, but the use of rituximab requires caution since the risk of life‐threatening infections such as sepsis accompanies agranulocytosis.…”
Section: Major Infectionsmentioning
confidence: 99%